PEMANFAATAN KARBON AKTIF DARI TEMPURUNG KELAPA DALAM MENURUNKAN KADAR AMONIA TOTAL DALAM AIR LIMBAH INDUSTRI - Nisa Nurhidayanti (DPPM Universitas Pelita Bangsa, 2020)
Entering the industry 4.0 stage, more industries are developing in Indonesia, one of which is PT Puradelta Lestari. PT Puradelta Lestari as a developer of the Deltamas city area that serves industrial, commercial and residential customers produces industrial liquid waste. Preliminary studies have shown that the ammonia content of wastewater in the PT has exceeded the threshold of 25 mg / L amonia. This study aims to determine the effect of adding activators to activated carbon from coconut shells with variations of immersion time on decreasing total ammonia levels in wastewater at PT. Puradelta Lestari. Activation of activated carbon is carried out with activators HCl, NaCl, and KOH with a concentration of 4%, with a volume ratio of activator 1: 6 and variations in the immersion time for 12 hours, 16 hours, 20 hours, 24 hours. The optimum condition was obtained at the time of immersion with KOH activator for 24 hours obtained a decrease in ammonia levels that is equal to 87.6%.